Evaluation of complementary foods from blends of roasted rice and soybean flours - OMAH ESTHER CHINELO; UMEGO EKENE CHRISTOPHER; ONAH PASCHAL CHUKWUDI; ONU DORIS ANULIKA (Innovare Journal of Food Sciences, 2017)
Objective: The study was carried out to evaluate the chemical and functional properties of complementary food produced from blends of rice and soybean flours. Methods: Rice and soybean grains were cleaned, de-hulled, roasted, winnowed and milled. The flours were used to formulated 90:10, 80:20, 70:30, 60:40 and 50:50 rice:soybean complementary food. The various blends of the rice:soybean complementary food were analysed for their proximate composition, vitamin and mineral content, anti-nutrient composition and sensory properties. Results: Moisture, protein, fat, fibre, ash and carbohydrate content of the blends ranged from 6.98-7.87, 5.70-19.15, 4.83-13.76, 0.41-1.39, 0.77-5.52 and 50.09-83.45% respectively. Mineral and vitamin contents of the rice-soybean complementary food blends ranged from 0.88-2.82 mg/100 g for Zn, 1.93-4.15 mg/100 g for Fe, 5.94-12.78 mg/100 g for Ca, 0.35-0.96 mg/100 g for vitamin B1 and 0.49-0.81 mg/100 g for vitamin B2. Bulk density, water absorption capacity and swelling capacity of the samples ranged from 0.83-0.89 g/cm3, 147.75-207.40% and 4.0-6.9 g/g respectively. Protein, fat, ash, mineral and vitamin contents of the rice-soybean complementary food blends showed an increase with increase in soybean addition. Anti-nutrient composition of the complementary food blends showed oxalate, phytate, haemagglutinin and tannin to be within safe levels. Conclusion: Blending of rice with soybean in various ratios for production of complementary food, affected the chemical, functional and sensory properties of the blends. Roasting of the grains before milling were instrumental in reducing the various anti-nutrients that are associated with rice and soybean to a minimum no- risk level.